2009
DOI: 10.1016/j.foodcont.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a bacteriocin-producing strain of Pediococcus acidilactici as a biopreservative for “Alheira”, a fermented meat sausage

Abstract: a b s t r a c tThis study was conducted to evaluate the ability of Pediococcus acidilactici HA-6111-2, a PA-1 bacteriocinproducing lactic acid bacterium (LAB), isolated from ''Alheira" to inhibit a cocktail of Listeria innocua strains during production and shelf-life of these products. The bacteriocinogenic culture reduced the Listeria population below the detection limit (1.5log CFU/g) and had no effect on the growth of the natural LAB flora or on the pH. Pathogenic organisms were not detected in any sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
5
22
3
2
Order By: Relevance
“…Interestingly, none of the P. acidilactici strains evaluated in our study showed resistance to any of the tested antibiotics. Moreover, none of them produced the virulence factors hemolysin or gelatinase, which is in agreement with previous studies (Albano et al 2009, Muñoz-Atienza et al 2013, Mabrouk et al 2014. In addition, the 8 tested strains did not display mucinolytic activity, indicating their low invasive and toxigenic potential at the mucosal barrier, which supports that LAB do not degrade mucin in vitro and is in agreement with previously published works (Zhou et al 2001, Delgado et al 2007, Muñoz-Atienza et al 2013.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, none of the P. acidilactici strains evaluated in our study showed resistance to any of the tested antibiotics. Moreover, none of them produced the virulence factors hemolysin or gelatinase, which is in agreement with previous studies (Albano et al 2009, Muñoz-Atienza et al 2013, Mabrouk et al 2014. In addition, the 8 tested strains did not display mucinolytic activity, indicating their low invasive and toxigenic potential at the mucosal barrier, which supports that LAB do not degrade mucin in vitro and is in agreement with previously published works (Zhou et al 2001, Delgado et al 2007, Muñoz-Atienza et al 2013.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, P. acidilactici strains were identified as low concentration tyramine producers in Robiola di Roccaverano cheese (Bonetta et al 2008), but other strains produced high tyramine concentrations in a sardine infusion decarboxylase broth (Küley et al 2013). In contrast, several studies showed that pediococcal strains isolated from fermented sausages (Fadda et al 2001, Albano et al 2009), traditionally processed fish products (Thapa et al 2006), and fish and fish products (Muñoz-Atienza et al 2011) were unable to produce tyramine, cadaverine, histamine, and/or putrescine. Interestingly, the respective genetic determinants in the 4 biogenicamine producing strains identified in our study were not detected by PCR analysis, which may be due to the existence of still unknown genes, to point mutations of the respective genes that could hamper their PCR-amplification, or to false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum 299v did not produce any of the virulence factors and genes tested, as well as for P. acidilactici HA‐6111‐2 as previously demonstrated by Albano et al . (). The absence of virulence factors of Lactobacillus and Pediococcus species has been reported by several authors (Vesterlund et al ., ; Borges et al ., ; Muñoz‐Atienza et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The liquefaction of the gelatine after cooling indicated a positive result of the reaction (Su et al 1991). The production of lipolytic enzymes, adapted from Albano et al (2009), was determined in BHI agar supplemented with 0.2% of sodium chloride (Biotec), 1.0% of Tween-80 (Merck, Darmstadt, Germany) and 0.005% of bromocresol green (Vetec, Rio de Janeiro, Brazil) at 37±1ºC for 48 h. The formation of clear zones around the colonies indicated a positive reaction.…”
Section: Characterisation Of the Probiotic Potential Of P Acidilactimentioning
confidence: 99%